2020
DOI: 10.3390/ijerph17113904
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Employment Program (SUPER) for Youth at Risk: A Conceptual and Practical Model

Abstract: This article describes the development, implementation, and evaluation of the transdisciplinary “Successful Pathways to Employment for youth at Risk” (SUPER) program to raise the transition readiness of youth at risk (YAR) from school into participation in adults’ responsibilities and employment. More than 10% of adolescents are at risk of dropping out of school following poor academic attainments. Schools appraise academic merit but do not develop relevant educational programs to prepare youth to transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Moreover, this strengthens their sense of self-efficacy. These findings are consistent with those of other studies in which the CIL model was used (Ivzori et al, 2020;Reiter, 2016;Shavit, 2015) and found to be effective in increased selfdetermination that including self-efficacy students with IDD.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this strengthens their sense of self-efficacy. These findings are consistent with those of other studies in which the CIL model was used (Ivzori et al, 2020;Reiter, 2016;Shavit, 2015) and found to be effective in increased selfdetermination that including self-efficacy students with IDD.…”
Section: Discussionsupporting
confidence: 92%
“…The transition from graduation to further education or paid employment requires specific skills to navigate and was identified by participants as challenging. This transition can be a vulnerable time for young people, particularly for those who may not have social support or role models and those who have limited understanding of the transition process [ 34 , 35 ]. The transition can also be influenced by factors such as structural changes in the economy, for example inflation and employment opportunities [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smyth and McConkey (2003) found that many of the young persons with severe learning disabilities in their study were able to articulate their future needs but that parents were, perhaps, less certain, o en wanting to support their ambitions but yet afraid that these may not be realisable. Ivzori et al (2020) in a study on transitions among young people at risk (YAR) consider that young people, in general, and YAR, in particular, lack work skills, habits, and knowledge about labor rights, realistic job opportunities, and ways to pursue career development a er school. Some studies emphasized that YAR either lack future aspirations (related to idealistic ideation) or experience a large gap between their future aspirations and expectations (a more realistic ideation).…”
Section: Envisioning the Futurementioning
confidence: 99%